2012
DOI: 10.1248/bpb.35.91
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Histamine in Exercise-Induced Fatigue: Favouring Endurance and Protecting against Exhaustion

Abstract: Exercise necessitates a large supply of O 2 and nutrients and rapid removal of CO 2 and waste products. Histamine is a regulator of the microcirculation (which performs these exchanges), suggesting a possible involvement of histamine in exercise. Histamine is released from either mast cells or non-mast cells. In the latter, histamine is newly formed via the induction of histidine decarboxylase (HDC) in response to an appropriate stimulus, and it is released without being stored. Here, in mice, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 31 publications
(43 reference statements)
4
35
0
Order By: Relevance
“…9,10,[14][15][16] To extend those observations, in the present study we histologically confirmed the induction of HDC protein by PMW. Immunostaining of HDC in mouse gastrocnemius muscle clearly indicated that PMW increases HDCpositive cells (Figs.…”
Section: Detection Of Hdc In Skeletal Muscles After Pmw Bysupporting
confidence: 82%
See 3 more Smart Citations
“…9,10,[14][15][16] To extend those observations, in the present study we histologically confirmed the induction of HDC protein by PMW. Immunostaining of HDC in mouse gastrocnemius muscle clearly indicated that PMW increases HDCpositive cells (Figs.…”
Section: Detection Of Hdc In Skeletal Muscles After Pmw Bysupporting
confidence: 82%
“…9,10) In the present study, by immunostaining skeletal muscles using a recently introduced commercial polyclonal anti-HDC antibody, we found that cells in the endomysium and around blood vessels, and indeed some muscle fibers themselves, became HDCpositive after PMW. In normal mice, the amount of histamine in the skeletal muscles, as in skin, is much higher (about 100 times) than that found in mast cell-deficient mice, 14) suggesting that skeletal muscles are rich in mast cells.…”
Section: -3)supporting
confidence: 54%
See 2 more Smart Citations
“…6) It is notable that muscle fatigue and pain are common factors among TMD, OP, and OA, and that histamine has been suggested to be causally involved in muscle fatigue and pain. [7][8][9] Collectively, these reports encourage the view that 1st AHs may indeed exert analgesic effects in patients with TMD, OP, and/or OA.…”
Section: )mentioning
confidence: 93%